Magic and Divination in Ancient Israel - Jeffers, Ann (Religion compass, 2007)
Despite officially condemning all magicians and divinatory practitioners, the Old Testament/Hebrew scriptures is replete with references to magic and divination. In an attempt to map out and understand the great variety of divinatory practices in the Old Testament/Hebrew Bible from techniques as varied as astrology, lot casting, necromancy or hepatoscopy to cite only a few, this article will re-examine the concept of ‘magic’ and re-evaluate the ways in which the Western world, especially since the nineteenth century, has viewed ‘magic’ as part of a series of dichotomies: religion vs. magic, science vs. magic; ‘magic’ is even seen as part of gender divisions (magic/women vs. religion/men). ‘Emic’ and ‘etic’ categories are also examined and a new definition situating magic as an ‘emic’ category is proposed: magic and divination are part of a complex system of religious intermediation where all the components of the cosmos interrelate. In this regard, ancient Israel shares the same worldview as its ancient Near Eastern neighbours and in particular a belief in cosmic forces originating and controlled by the dominant deity or deities. While the rational underpinning of such practices are examined (and questions about control and gender touched upon), it is also argued that a proper understanding of magic and divination in ancient Israel can only be viewed as an integral part of its cosmology. An ‘emic’ definition of magic suggests its connection with Torah and wisdom.